2018
DOI: 10.1111/cod.13136
|View full text |Cite
|
Sign up to set email alerts
|

Nickel deposition and penetration into the stratum corneum after short metallic nickel contact: An experimental study

Abstract: Background: Knowledge about the skin deposition and penetration of nickel into the stratum corneum (SC) after short contact with metallic items is limited.Objective: To quantify nickel skin deposition and penetration into the SC after short contact with metallic nickel.Methods: Sixteen nickel-allergic participants and 10 controls were exposed to 3 pure nickel discs and 1 aluminium disc on each volar forearm for 3 × 10 minutes. Before exposure, 1 forearm was irritated with 0.5% sodium lauryl sulfate under 24-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 28 publications
0
45
1
1
Order By: Relevance
“…Nickel skin exposure (μg/cm 2 ) has been measured in nails and in the skin with various types of wipe sampling, finger immersion, and tape stripping . Following sampling, the nickel content is analysed, for example, by inductively coupled plasma mass spectrometry.…”
Section: Exposure Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nickel skin exposure (μg/cm 2 ) has been measured in nails and in the skin with various types of wipe sampling, finger immersion, and tape stripping . Following sampling, the nickel content is analysed, for example, by inductively coupled plasma mass spectrometry.…”
Section: Exposure Quantificationmentioning
confidence: 99%
“…Historically, prolonged metal‐skin contact has been expected to be required for critical nickel skin deposition . However, more recently, rapid skin deposition following contact has been shown to occur after seconds to minutes . Erfani et al found that 4.7 μg of nickel per cm 2 was deposited onto the fingertip following 3 seconds of contact with metallic nickel, and Ahlström et al showed nickel skin doses of 10.1 to 23.5 μg/cm 2 after three 10‐minute exposures .…”
Section: Nickel Skin Depositionmentioning
confidence: 99%
“…Furthermore, Nixon et al state that the nickel elicitation threshold is linked specifically to the duration of exposure, as it requires corrosion of the material to release nickel ions. However, this statement is incorrect, as high amounts of nickel are, indeed, deposited within seconds and minutes of skin contact …”
mentioning
confidence: 99%
“…Without any supporting literature, Nixon et al claim that nickel skin doses needed to elicit allergic nickel dermatitis may rarely be exceeded by contact with nickel‐releasing metallic items. However, substantial nickel skin doses capable of eliciting allergic nickel dermatitis have been measured following both experimental and real‐life occupational exposure to nickel‐containing materials . We are concerned that Nixon et al misleadingly discuss and cite a study by Jensen et al, in which considerable nickel skin doses were found on the hands after the performance of normal work tasks for 2 hours.…”
mentioning
confidence: 99%
See 1 more Smart Citation